Peripheral T cell responses to immunotherapy treatment in metastatic melanoma - Woodcock, V (2019)
Immune checkpoint inhibitor treatment has revolutionised treatment for cancers such as malignant melanoma, producing durable responses in patients with metastatic malignancy. Despite this progress, responses are still only seen in a subset of patients and the phenotype and specificity of the T cells responsible for determining efficacy remain poorly characterised. A better understanding of T cell behaviour during immunotherapy treatment is required to identify markers of response and resistance and to predict effective combination strategies. To address this, we performed longitudinal peripheral immune monitoring of metastatic melanoma patients receiving checkpoint inhibitor therapy. By integrating a variety of single-cell analysis approaches including mass cytometry, MHC Class I tetramer staining, single-cell fluorescence activated cell sorting and single-cell RNAsequencing, we were able to track and analyse in detail tumour-specific T cell responses in the periphery over time. Accumulation of activated effector CD8+ T cells expressing CD38 and HLA-DR was observed in response to treatment, was more pronounced with combination anti-CTLA-4/anti-PD-1 treatment than anti-PD-1 monotherapy, and was correlated with treatment outcome. Activated cells were enriched in tumour-specific compared to microbial-specific T cells, with diversification and expansion of the tumour but not microbial-specific response observed over the course of treatment. This was accompanied by transient alterations in the functional avidity of T cell clones specific for the common tumour-associated antigen MART-1. Single-cell RNA-seq revealed substantial heterogeneity in the transcriptional profile of tumour-specific T cells during therapy with transient activation and persistence of specific clonotypes observed. These results demonstrate both the feasibility of monitoring tumour-specific T cells mobilised in response to immunotherapy in the periphery, and provide insights into the mechanisms underpinning therapeutic efficacy of combination checkpoint blockade. The results also have implications for the identification of T cells and TCR clonotypes with maximum therapeutic potential for other therapeutic strategies such as adoptive cell therapies.